Progestogens in menopausal hormone therapy - Małgorzata Bińkowska; Jarosław Woroń (Menopause Review, 2015)
Progestogens share one common effect: the ability to convert proliferative endometrium to its secretory form. In contrast, their biological activity is varied, depending on the chemical structure, pharmacokinetics, receptor affinity and different potency of action. Progestogens are widely used in the treatment of menstrual cycle disturbances, various gynaecological conditions, contraception and menopausal hormone therapy. The administration of progestogen in menopausal hormone therapy is essential in women with an intact uterus to protect against endometrial hyperplasia and cancer. Progestogen selection should be based on the characteristics available for each progestogen type, relying on the assessment of relative potency of action in experimental models and animal models, and on the indirect knowledge brought by studies of the clinical use of different progestogen formulations. The choice of progestogen should involve the conscious use of knowledge of its benefits, with a focus on minimizing potential side effects. Unfortunately, there are no direct clinical studies comparing the metabolic effects of different progestogens.